2022
DOI: 10.3389/fnins.2022.949138
|View full text |Cite
|
Sign up to set email alerts
|

The sense of agency in emerging technologies for human–computer integration: A review

Abstract: Human–computer integration is an emerging area in which the boundary between humans and technology is blurred as users and computers work collaboratively and share agency to execute tasks. The sense of agency (SoA) is an experience that arises by a combination of a voluntary motor action and sensory evidence whether the corresponding body movements have somehow influenced the course of external events. The SoA is not only a key part of our experiences in daily life but also in our interaction with technology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 175 publications
0
10
0
Order By: Relevance
“…With the rapid development of science and technology, flexible wearable sensors have been utilized as core components of signal acquisition, thereby stimulating great research interest and wide application in fields of bioelectronic devices [1,2], smart homes [3], electronic skin [4][5][6], intelligent robotics [7,8], and human-computer interaction [9,10], among others. According to the working mechanism, flexible pressure sensors can be divided into piezoresistive [11][12][13], capacitive [14], piezoelectric [15], and triboelectric [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of science and technology, flexible wearable sensors have been utilized as core components of signal acquisition, thereby stimulating great research interest and wide application in fields of bioelectronic devices [1,2], smart homes [3], electronic skin [4][5][6], intelligent robotics [7,8], and human-computer interaction [9,10], among others. According to the working mechanism, flexible pressure sensors can be divided into piezoresistive [11][12][13], capacitive [14], piezoelectric [15], and triboelectric [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…People rely on their brains to recognize the world, learn knowledge, and summarize rules. Their brains also allow them to use memory systems to store the information generated when experiencing different events (Atkinson and Shiffrin, 1968 ; Cornelio et al, 2022 ). In turn, the information serves as prior knowledge, helping people in dealing with similar problems better and adapting to new complex scenes faster.…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancements in biosensing have made it possible to reveal hidden physiological data (biosignals), which can provide valuable insights into others' emotional and cognitive states [48]. This relates to recent eforts toward sensible human-computer integration [7,21,41], where one may sense information that is otherwise difcult to perceive and recognize due to physical or cognitive limitations, or otherwise normally hidden during face-to-face interactions. Researchers have found that "expressive" biosignals, when displayed as a social cue, have the potential to enhance interpersonal communication and increase interoceptive awareness [15,29,36], which can help us better recognize and express our own and others' emotional and physical states across real [13,14,20,31,37] and virtual reality environments [22,27,52].…”
Section: Introductionmentioning
confidence: 99%